Over 20% Efficient and Stable Non‐Fullerene‐Based Ternary Bulk‐Heterojunction Organic Solar Cell with WS2 Hole‐Transport Layer and Graded Refractive Index Antireflection Coating. Issue 6 (10th May 2020) - Ram, Kiran Sreedhar; Singh, Jai
Abstract: The power conversion efficiency (PCE) of a ternary organic solar cell (TOSC) with an active layer consisting of PBDB‐T‐2F and two non‐fullerene materials Y6 and SF(BR)4 is simulated. Tungsten disulphide (WS2 ) is used as the hole transport layer (HTL) to reduce the contact resistance between the active layer and anode which enhances the internal quantum efficiency to 91.7%. It is found that the use of a highly absorbing non‐fullerene small molecule acceptor, SF(BR)4, enhances the absorption as well as improves the stability. Finally, the incorporation of the graded refractive index coating, in the form of moth‐eye shaped nanostructures, on the top of glass reduces the reflection losses and enhances the transmission coefficient from 0.88 to 0.94. Thus, the TOSC simulated here, of the structure moth‐eye‐AR/glass/ITO/WS2 /PBDB‐T‐2F:Y6:SF(BR)4 /PFN‐Br/Al, produces a PCE of 20.87%. The results presented in this paper are expected to provide useful guidance for fabricating highly efficient and stable hybrid bulk‐heterojunction solar cells. Abstract : Introduction of the non‐fullerene acceptor SF(BR)4 enhances the photon absorption in the region from 450 to 550 nm, and incorporation of the antireflection coating of graded refractive index of moth‐eye nanostructures reduces the reflection losses. Thus, a modified ternary organic solar cell (TOSC) with the structure moth‐eye‐AR/Glass/ITO/WS2 /PBDB‐T‐2F:Y6:SF(BR)4 /PFN‐Br/Al produces a simulated power conversion efficiency of 20.87%.